Pengaruh Service Excellence dan Fasilitas Wisata terhadap Pengalaman Wisatawan (Tourist Experience) di Sendang Kun Gerit Kabupaten Sragen Jawa Tengah - Oneng Setya Harini; Faradila Anggun Surya Rini; Matius Tinna Sarira; Mohamad Nur Afriliandi Nasution; Muhammad Syauqi (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze the influence of service excellence and tourism facilities on the experience of tourists visiting Sendang Kun Gerit, Gemolong, Sragen, Central Java. The research method used is quantitative with primary data collection through questionnaires. The population in the study were tourists who had visited Sendang Kun Gerit with a sample of 105 tourists. Data analysis was carried out by multiple linear regression using SPSS 29. The results showed that service excellence and tourism facilities had a positive and significant effect on tourist experience. The coefficient of determination test indicated that 84.5% of the variation in tourist experience could be explained by service excellence and facilities variables, while the remaining 16.5% was influenced by other factors not examined in this study. These results indicate that improving service excellence and tourism facilities can increase the attractiveness of Sendang Kun Gerit as a tourist destination. Therefore, tourism managers need to pay attention to good excellent service and improving tourism facilities to increase the number of tourist visits.